Typos’ Effects on Web-Based Programming Code Output: A Computational Linguistics Study - Iksora; Arafah, Burhanuddin; Syafruddin, Syanuwalini; Muchtar, Jumardin; Lestari, Puji Ayu (Theory and practice in language studies, 2022)
Computational linguistics is concerned with understanding language from a computational perspective and constructing artifacts that are useful in processing and generating language. In the use of language, whether human language or programming language, there can be an error that makes the language not understood properly. One of the errors that often occurs is syntax error. In language, a syntax error is a mistake in using a language that involves organizing words and phrases that do not make sense. While in programming, a syntax error is an error in writing code in a program that makes the format or information unrecognizable by the computer system. Such errors are the simplest of errors but can affect many aspects of the final code output. This article aims to show how writing errors or typos in programming code can affect some or all of the results. The data obtained is data from web programming code that is used to make the website display the Geographic Information System Clustering the Distribution of Stunting Disease in Banggai Regency with K-Means, and also the R programming code used to calculate the stunting distribution using K-Means. The results of this article will show that a typo, even just a letter or any single punctuation, can affect the program’s final result.